Neural Signature of Buying Decisions in Real-World Online Shopping Scenarios – An Exploratory Electroencephalography Study Series - Horr, Ninja K.; Han, Keren; Mousavi, Bijan; Tang, Ruihong (Frontiers in Human Neuroscience, 2022)
The neural underpinnings of decision-making are critical for understanding and predicting human behaviour. However, findings from decision neuroscience are limited in their practical applicability due the gap between experimental decision-making paradigms and real-world choices. The present manuscript investigates the neural markers of buying decisions in a fully natural purchase setting: Participants are asked to use their favourite online shopping applications to buy common goods they are currently in need of. Their EEG is recorded while they view the product page for each item. EEG responses to pages for products that are eventually bought are compared to those that are discarded. Study 1 repeats this procedure in 3 batches with different participants, product types and time periods. In an explorative analysis, two neural markers for buying compared to no-buying decisions are discovered over all three batches: Frontal alpha asymmetry peak and frontal theta power peak. Occipital alpha power at alpha asymmetry peaks differs in only one of the three batches. No further significant markers are found. Study 2 compares the natural product search to a design in which subjects are told which product pages to view. In both settings, frontal alpha asymmetry peak is increased for buying decisions. Frontal theta peak increase is replicated only when subjects search through product pages by themselves. The present study series represents an attempt to find neural markers of real-world decisions in a fully natural environment and explore how those markers can change due to small adjustments for the sake of experimental control. Limitations and practical applicability of the real-world approach to studying decision-making are discussed.